2019
DOI: 10.1139/cjfr-2018-0052
|View full text |Cite
|
Sign up to set email alerts
|

Selecting for stable and productive families of Eucalyptus urophylla across a country-wide range of climates in Brazil

Abstract: To identify stable and productive Eucalyptus urophylla S.T. Blake families across diverse climate zones in Brazil, we evaluated growth and survival of 322 open-pollinated families derived from 13 genetically improved seed sources in 10 trials across the country. Survival and growth data were analyzed using linear mixed models and REML/BLUP. Survival ranged from 51% to 92%, and the mean annual increment varied from 19 to 46 m3·ha−1·year−1. Although planted in suitable climatic zones, some trials had low surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…DBH heritability within each site range from 0.19 to 0.39 is considered intermediate for this growth character. This range is similar to improved E. urophylla families evaluated across ten sites in Brazil (Silva et al 2019), with a range from 0.09 to 0.29, considering mixed mating. The highest DBH heritability was obtained in Itamarandiba-MG, indicating lower environmental effects on phenotypic variation.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…DBH heritability within each site range from 0.19 to 0.39 is considered intermediate for this growth character. This range is similar to improved E. urophylla families evaluated across ten sites in Brazil (Silva et al 2019), with a range from 0.09 to 0.29, considering mixed mating. The highest DBH heritability was obtained in Itamarandiba-MG, indicating lower environmental effects on phenotypic variation.…”
Section: Resultssupporting
confidence: 75%
“…This corroborates results of Rodas et al (2005) that when E. grandis is grown as a pure species, it is not well adapted to the Am climatic condition in Monte Dourado, where high temperatures and humidity favor Cylindrocladium leaf disease. In this site, the disease attacks the trees since the first summer (wet and hot) and probably is the main mortality cause of susceptible material in the climatic conditions of the site, as discussed by Silva et al (2019).…”
Section: Resultsmentioning
confidence: 94%
“…Our results agree with those reported by Silva, et al (2019a;2019b) when evaluating survival and growth in 3-year progeny trials of E. urophylla and E. grandis in different climatic zones of Brazil. These authors reported a survival rate of 51 % to 92 % and an MAI of 19 to 46 m 3 •ha -1 •year -1 for E. urophylla and of 28 to 89 % and 20.5 and 48.4 m 3 • ha -1 •year -1 for E. grandis.…”
Section: Discussionsupporting
confidence: 92%
“…Nine Eucalyptus species dominate hardwood plantations around the world due to their fast growth under a wide range of environmental conditions (Harwood, 2011;Müller da Silva et al, 2019), providing considerable capacity as sinks for atmospheric C (e.g., Binkley et al, 2017;Viera and Rodríguez-Saolliero, 2019). One of the most important eucalypt species used in plantations is E. grandis Hill ex Maid (comm.…”
Section: Introductionmentioning
confidence: 99%